Tren Penelitian Global Pemanfaatan Limbah Abu Terbang Batubara (Coal Fly Ash): Analisis Bibliometrik Menggunakan Database Pengindeks Scopus - Intan Abdillah Arrasyid; M. Nurcholis; Shofa Rijalul Haq (Mining Science And Technology Journal, 2026)
This study presents a systematic bibliometric review of global research trends in coal fly ash (CFA) utilization between 2015 until 2025, drawing data from the Scopus database. The analysis reveals a notable increase in publications, particularly a sharp surge in 2023 and 2024, indicating growing urgency regarding sustainable industrial waste management. Geographically, China leads research contributions, aligning with its role as a major coal producer, followed by Poland, the United States, and India, underscoring the topic's relevance across diverse global applications, from construction to environmental remediation. Research focus is broadly distributed across several key fields, including environmental science, materials science, and energy. Prominent topics identified remediation of environmental concerns, carbon emission mitigation efforts through combustion processes, and the development of innovative materials such as cement and zeolites using CFA as an alternative component. The central position of "fly ash" as a core keyword in the thematic network underscores its centrality in exploring the potential of this valuable by-product. This review aims to provide comprehensive insights for the scientific community, policymakers, and industrial sectors regarding current research dynamics and prospective directions in CFA utilization.